2005
DOI: 10.1093/geronb/60.2.s102
|View full text |Cite
|
Sign up to set email alerts
|

Religious Attendance and Mortality: An 8-Year Follow-Up of Older Mexican Americans

Abstract: Our findings suggest that weekly church attendance may reduce the risk of mortality among older Mexican Americans. Future research should focus on identifying other potential mediators of the relationship between religious involvement and mortality risk in the Mexican-origin population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(76 citation statements)
references
References 66 publications
6
68
0
2
Order By: Relevance
“…Further inquiry of this issue is, thus, warranted. The second major Wnding of note is the association between synagogue attendance and survival, supporting other studies that have found attendance at a place of worship to enhance survival in later life (Hill et al 2005;la Cour et al 2006). Church attendance is viewed in the Berkman model as a form of social engagement, one of the psychosocial mechanisms that are shaped by social network structure and interaction.…”
Section: Discussionsupporting
confidence: 75%
“…Further inquiry of this issue is, thus, warranted. The second major Wnding of note is the association between synagogue attendance and survival, supporting other studies that have found attendance at a place of worship to enhance survival in later life (Hill et al 2005;la Cour et al 2006). Church attendance is viewed in the Berkman model as a form of social engagement, one of the psychosocial mechanisms that are shaped by social network structure and interaction.…”
Section: Discussionsupporting
confidence: 75%
“…In a meta-analytic review of 42 independent effect sizes, McCullough, Hoyt, Larson, Koenig, and Thoresen (2000) discovered that people who were highly religious were, on average, 29% more likely to be alive at any given follow-up point than were less religious people (95% confidence interval: 1.20 to 1.39). In a traditional narrative review of studies considered by the authors to be of high quality (e.g., studies with large, representative samples and adequate statistical control of potential confounds), Powell, Shahabi, and Thoresen (2003) likewise concluded that frequent religious service attendance was associated with a 25% reduction in mortality.Studies published after McCullough et al's (2000) and Powell et al's (2003) reviews have yielded similar conclusions in random samples of U.S. adults (Musick, House, & Williams, 2004); older Mexican Americans (T. D. Hill, Angel, Ellison, & Angel, 2005); and adults in Denmark (la Cour, Avlund, & Schultz-Larsen, 2006), Finland (Teinonen, Vahlberg, Isoaho, & Kivela, 2005), and Taiwan (Yeager et al, 2006). These latter studies have also revealed 25% to 30% reductions in mortality for religiously active people, even after controlling for reasonable sets of potential confounds and explanatory variables.…”
mentioning
confidence: 79%
“…Recent studies have demonstrated health benefits of religious involvement for older adults (Benjamins 2004;George, Ellison, and Larson 2002;Hill et al 2005), with some studies © 2008 SAGE Publications. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…With the anticipated growth in the older population, the number of elders with limitations is expected to rise to 21 million by 2030 and 25 million by 2050 (Shirey and Summer 2000). Such increases will result in greater costs for Medicare and Medicaid and other publicly funded programs.Recent studies have demonstrated health benefits of religious involvement for older adults (Benjamins 2004;George, Ellison, and Larson 2002;Hill et al 2005), with some studies © 2008 SAGE Publications. All rights reserved.…”
mentioning
confidence: 99%